2017
DOI: 10.1371/journal.pone.0171481
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 molecular epidemiology among newly diagnosed HIV-1 individuals in Hebei, a low HIV prevalence province in China

Abstract: New human immunodeficiency virus type 1 (HIV-1) diagnoses are increasing rapidly in Hebei. The aim of this study presents the most extensive HIV-1 molecular epidemiology investigation in Hebei province in China thus far. We have carried out the most extensive systematic cross-sectional study based on newly diagnosed HIV-1 positive individuals in 2013, and characterized the molecular epidemiology of HIV-1 based on full length gag-partial pol gene sequences in the whole of Hebei. Nine HIV-1 genotypes based on fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 31 publications
8
24
0
Order By: Relevance
“…The overall prevalence of TDR among residents newly diagnosed with HIV infection in Beijing was low. There was a apparent declining trend during study period, which was consistent with the results of other molecular diversity studies in other provinces of China [15][16][17]19,20]. There was no significant difference in the prevalence of TDR when comparing the sex, the age, the transmission risk groups and the ethnicity of the study population.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The overall prevalence of TDR among residents newly diagnosed with HIV infection in Beijing was low. There was a apparent declining trend during study period, which was consistent with the results of other molecular diversity studies in other provinces of China [15][16][17]19,20]. There was no significant difference in the prevalence of TDR when comparing the sex, the age, the transmission risk groups and the ethnicity of the study population.…”
Section: Discussionsupporting
confidence: 89%
“…The trends for CRF01_AE and CRF07_BC increased over time, whereas B had a decreasing trend. A similar trend was observed in other provinces across China [15][16][17]. Indeed, Beijing is a popular destination for floating populations that come from other provinces and other countries.…”
Section: Discussionsupporting
confidence: 77%
“…Therefore, our study described the prevalence of surveillance drug‐resistant HIV‐1 strains at 2.1% among the drug‐naïve population in Jiangmen, below the threshold of 5% (the WHO HIVDR Threshold Surveillance protocol). Interestingly, NNRTIs‐related DRMs V179D/E occurred the most frequently among the untreated population in our study, which was coincident with the previous research 4,31,32 . Contrary to V179D/E highly occurring in CRF01_AE, our study showed that V179D/E tended to be found in CRF55_01B strains, implied that DRMs such as V179D/E were shown diversified among the drug‐ naïve population.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, sexual behaviors, condom use, male circumcision, antiretroviral therapy and sharing syringes among drug users all have different impacts on HIV/AIDS prevalence (Zhang et al, 2008;Nikolopoulos and Bonovas, 2017;Kelly et al 2017). A series of studies on HIV/AIDS prevalence in the United States (Rios-Gonzalez and Flores-Enriquez, 2018), China (Yuan et al, 2018;Yang et al, 2017;Lu et al, 2017;Tang et al, 2016;Pan et al, 2016), Africa (Scriven et al, 2016), Germany (Stecher et al, 2018) and Ukraine (Vasylyeva et al, 2018) have been published, but rare national studies were reported about the impacts of regional and age differences on clinical epidemiology of HIV/AIDS. Considerable changes of related policies have been provided including the implementation of innovative strategies and a comprehensive anti-HIV program over the last 20 years in China.…”
Section: Introductionmentioning
confidence: 99%